O ensino por meio da educação a distância no sistema carcerário baiano como mecanismo de ressocialização - Barbosa, Fernanda Graziella Bispo (2021)
This study aims to analyze the educational system in prisons in Bahia and also deals with the use of technologies available in society to promote the process of resocialization of inmates in the prison system through distance higher education, demonstrating its positive and negative aspects. Throughout the evolution of humanity, the penal system has adapted to new ways of thinking and the deprivation of liberty has emerged as a change in paradigms and defense of human rights inherent to each individual. The failure to structure the prison system is still a recurring problem. There are many situations that affect the dignity of the prisoner and violate their rights. Resocialization is a constitutional right guaranteed to every citizen, as is education, which is also expressly provided for in the Penal Execution Act. In this study, the right and the importance of higher education in the process of re-socialization of the prisoners and ex-prisoners of the Bahian prison system will be addressed, as well as the viability of the distance higher-education system to promote the resocialization process of the inmates. It is the right of prisoners to access education in the prison system, a right ensured by national and international legislation. Considering the structural precariousness of the Bahian penitentiary system, higher distance education is an effective way to enable the implementation of higher education in prisons, without a greater structural and personal burden. The importance of offering continued educational training to prisoners is intended to contribute directly to educational and professional training, to their social reintegration, observing the principle of human dignity and the right to education.